The Impact of Allosteric Learning on Students’ Academic Achievement and Research Skills in the 5th Grade Social Studies Course - Hüseyin Bayram (Universitas Pendidikan Indonesia, 2022)
Allosteric learning approach advocates the acquisition of knowledge through experiences, and this could be appropriate for social studies course since its content is based on daily life. This study was conducted in a middle-school located in a province of Turkey during the fall-semester of the 2021-2022 academic year. The study investigated the impact of allosteric learning on 5th grade learners’ academic achievement and research skills in social studies course. Moreover, the participating learners’ views on the impact of allosteric learning on their academic achievement and research skills were also explored. The mixed embedded design was employed in the study. The participants consisted of 48 students, 23 in the experimental and 25 in the control group. To collect data, Science, Technology and Society Achievement Test, Research Skills Test, and interview form were employed. For analysis, t-test for independent samples, covariance analysis, and content analysis were used. It was found that the social studies course carried out within the scope of the allosteric learning approach increased students’ academic achievement and improved their research skills. In addition, students believed that allosteric learning increased their academic achievement and equipped them with research skills.